Reflections on Justice and the Robot Tax: Should We Tax Automation to Save Jobs? - Moser, Elias (Momentum Quarterly, 2021)
A current policy proposal to address the problem of technological unemployment is to impose a tax on labor replacing technologies. The idea is to preserve jobs by disincentivizing automation. In this article, I analyze the proposal normatively. I show that, with respect to conceptions of distributive justice, it is unclear whether it is justified to decrease consumers’ potential real income gains from automation. But foremost, my critique is based on an examination of the moral ideal behind the normative claim to preserve work. I show that arguments in favor of a robot tax rest on dubious moral beliefs about the value of work, and I conclude that a moral argument for imposing a robot tax is subject to legitimate scrutiny.
Keywords: Technological Unemployment; Automation Tax; Distributive Justice; Value of Work; Universal Basic Income